LIVER FIBROSIS AND METABOLIC CHANGES IN NON-ALCOHOLIC FATTY LIVER DISEASE: MODERN APPROACHES TO DIAGNOSTICS - Parpiboyeva D.A., Musayeva M.A. (Central Asian Journal of Medicine, 2025)
This study is devoted to the assessment of metabolic changes and the degree of liver fibrosis in patients with non-alcoholic fatty liver disease (NAFLD), including steatosis of varying degrees. The study included 90 patients with NAFLD and 45 people in the control group. Research methods: clinical and laboratory methods, ultrasound elastometry (FibroScan), DEBQ questionnaire to identify eating disorders, molecular genetic analysis of the expression level of microRNA-221.